19B isotope as a 17B-n-n three-body cluster close to unitary limit. (December 2020) - Carbonell, J.; Hiyama, E.; Lazauskas, R.; Marqués, F. M.
Abstract: We describe 19 B in terms of a 17 B- n - n three-body system, where the two-body subsystems 17 B- n and n - n are unbound (virtual) states close to the unitary limit. The energy of 19 B ground state is well reproduced and two low-lying resonances are predicted. Their eventual link with the Efimov physics is discussed. This model can be extended to describe the recently discovered resonant states in 20, 21 B.